Joe Moakley's Journey : From South Boston to El Salvador - Schneider, Mark R. (Mark Robert), 1948- (Book collections on Project MUSE., 2013)
A biography of the popular, long-serving congressman from South Boston. In November 1989 in El Salvador, six Jesuit priests and their two female housekeepers were rousted from their beds and shot as they lay face down on the ground. At first, the George H. W. Bush administration echoed the Salvadoran military's line that the rebels must have done it. When House Speaker Tom Foley tasked a senior congressman with investigating the murders, the people of El Salvador found an unlikely champion in the person of John Joseph Moakley, representative from South Boston. In this biography, the author charts one of the most unusual transformations in American politics. A native son of South Boston, Moakley was an effective and influential House member, whose greatest influence and legacy is, paradoxically, far from home in the fields of El Salvador and Central America. Though firmly, fiercely grounded in his hometown of South Boston - he never lived anywhere else - from the beginning of this investigation until his death in 2001, issues of Central American justice, peace, and economic development became Joe Moakley's cause.